Diversity and Co-occurrence Patterns of Soil Bacterial and Fungal Communities in Seven Intercropping Systems - Li, Sen; Wu, Fengzhi (Frontiers in Microbiology, 2018)
Intercropping plays an important role in greenhouse production and affects soil physicochemical properties and soil microbial community structure, but influences of intercropping on the relationship of microorganisms are reported in continuous cropping soil rarely. Here, we investigated the effects of seven intercropping systems [alfalfa (Medicago sativa L.)/cucumber, trifolium (Trifolium repens L.)/cucumber, wheat (Triticum aestivum L.)/cucumber, rye (Secale cereale L.)/cucumber, chrysanthemum (Chrysanthemum coronrium L.)/cucumber, rape (Brassica campestris L.)/cucumber, mustard (Brassica juncea L.)/cucumber] on soil bacterial and fungal communities compared to the cucumber continuous cropping system in the greenhouse. The results showed that intercropping significantly increased microbial OTU richness and Shannon diversity. Nevertheless, there was no significant difference between intercropping and monoculture in the soil microbial community structure. Redundancy analysis indicated that soil microbial community composition was indirectly influenced by soil properties. In addition, cooccurrence network analysis demonstrated that simple inter-relationships of fungal taxa were observed in the intercopping soil, and bacterial taxa was just inverse in trifolium, wheat, and mustard soil, others were similar with fungal taxa, suggesting that soil microbial co-occurrence patterns were affected by intercropping. Taken together, intercropping had a highly significant influence on soil bacterial and fungal communities diversity, though did not shape notably soil microbial community structure, and strongly changed the relationships of microbial taxa.